Economists on Samuelson and Solow on the Phillips curve - Forder, J (University of Oxford, 2010)
Samuelson and Solow published a widely read paper in the May issue of the American Economic Review of 1960. It discussed the causes of inflation, the Phillips curve, and related matters. Discussion of their paper frequently says that it presented the Phillips curve as a stable, exploitable relation, and hence played an important role in the development of inflationary policy. This is hardly so. Sometimes authors notice this, but they nevertheless say it was misread as advocating inflationary policy and hence played the same role in policy development. Close attention to what was said about it in the relevant period – the 1960s – reveals that it was not then seen as advocating inflationary policy at all. This raises a strange puzzle as to why it was that, rather suddenly, it came to be incorrectly said that Samuelson and Solow had been interpreted as being inflationist when they neither were that, nor had been interpreted in that way.